2021
DOI: 10.1002/brb3.2336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of safinamide on pain in patients with fluctuating Parkinson's disease

Abstract: Background: Non-motor symptoms (NMS) are integral to Parkinson's Disease (PD) and management remains a challenge. Safinamide is a novel molecule in relation to addressing NMS due to its multifocal mechanism of action with both dopaminergic and nondopaminergic properties. Objective: To investigate the efficacy of safinamide on NMS and its burden in PD patients with motor fluctuations after 6 months of treatment. Methods: This observational, multicenter, open-label, pilot study assessed a wide range of NMS using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…In a multicenter, double-blind, placebo-controlled RCT 38 and two open-label prospective studies 43 , 44 , safinamide 100 mg for advanced PD patients did not significantly ameliorate depression at 6 months. However, in the Study 016 and its extension study (Study 018), significant benefits on the Hamilton Depression Scale (HAMD) and PDQ-39 emotional well-being subscore over placebo were observed with safinamide 100 mg but not with the 50 mg dose 37 , 39 .…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In a multicenter, double-blind, placebo-controlled RCT 38 and two open-label prospective studies 43 , 44 , safinamide 100 mg for advanced PD patients did not significantly ameliorate depression at 6 months. However, in the Study 016 and its extension study (Study 018), significant benefits on the Hamilton Depression Scale (HAMD) and PDQ-39 emotional well-being subscore over placebo were observed with safinamide 100 mg but not with the 50 mg dose 37 , 39 .…”
Section: Resultsmentioning
confidence: 93%
“…All the studies of safinamide enrolled advanced PD patients 37 46 except for one study for those with high non-motor burden (defined as the NMS Scale (NMSS) ≥ 40) 25 . RCTs and open-label studies using safinamide 100 mg reported positive or negative QOL outcomes with safinamide 25 , 37 40 , 42 , 43 , 45 , 46 , whereas all the studies using safinamide 50 mg reported negative outcomes 37 , 39 , 40 , 44 . Based on the PDQ-39 outcomes from the RCTs, effect sizes for safinamide 100 mg and 50 mg were small (0.22–0.23) and trivial (0.11–0.15), respectively.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations